Did the Basel Accord Cause a Credit Slowdown in Latin America? - Cosimano, Thomas (IMF Working Papers; Working Paper ;, 2005)
Drawing from a unique data set comprising 2,893 banks and 152 countries over the period 1987 to 2000, we test whether the adoption of the Basel Accord by Latin American and Caribbean countries was responsible for the serious slowdowns in credit growth experienced by these countries. We find that, on average, both bank capitalization and lending activities in Latin America increased after Basel. Consequently, Basel did not seem to lead to an overall credit decline. However, we do find evidence that loan growth became more sensitive to some risk factors. Our study suggests that the upcoming adoption of Basel II might cause greater procyclicality of credit.